Islamic Capital Market Responses to Political Events: Evidence from Indonesia - Rahmanda Fidelia; Putri Rosiyani; Inne Fajar Luqyana; Abiyyu Achmad Syahru Mubarok; Nur Hidayah (Jurnal Ekonomi Syariah Teori dan Terapan, 2024)
The research aims to find and see whether the impact of political activities has on the trading volume of shares recorded on the Indonesian Sharia Stock Index (ISSI). The research method uses a quantitative approach focuses on event studies by looking at actual trends. The secondary data used comes from the official page which contains stock price data and trading volume. Results of the research confirms that there are differences in trading volume that occured in ISSI shares during the election period. Only in the 2014 election did ISSI shares show no difference between pra and pasca the event. This means that ISSI shares are quite stable in the face of political dynamics that occur.